Brief Report: Barriers to Treatment Adherence in Pediatric Inflammatory Bowel Disease - Hommel, Kevin A. (Oxford University Press, 2010)
Objective To examine perceived barriers to medication adherence in inflammatory bowel disease (IBD) treatment and their relationship with adherence using a combined forced choice and semi-structured interview assessment approach. Methods Sixteen adolescents with IBD and their parents participated in an open-ended interview regarding adherence barriers and completed quantitative measures of adherence, barriers to treatment, and disease severity. Results The most commonly identified barriers to adherence were forgetting, interference with other activities, difficulty swallowing pills, and not being at home. Number of reported barriers was positively correlated with objective nonadherence for 6-MP/azathioprine. Nonadherence frequency was 42% for 6-MP/azathoprine and 50% for 5-ASA medications. Conclusions Using a combined assessment approach, patients and parents reported several barriers to treatment adherence that are appropriate for clinical intervention. This is critical given the significant medication nonadherence observed in this sample and the relationship between total number of barriers and disease management problems.